Social gamers’ everyday (in)visibility tactics: playing within programmed constraints - Willson, Michele; Kinder-Kurlanda, Katharina (Taylor & Francis, 2019)
As continual scandals around internet data collection, manipulation and dissemination (the Snowden disclosures, the Facebook emotion contagion research and more recently, the Cambridge Analytica revelations) have made resoundingly apparent, activity online – because it is online – can be mapped, managed and manipulated. How well everyday users understand and manipulate the possibilities, constraints and imperatives of the programmed environments within which they operate may be able to be discerned through a closer examination of actions within the sphere of social game play. We are interested in how gamer awareness of programmed requests to engage, divulge information, connect to other users alongside broader privacy concerns are navigated and translated into specific tactical behaviours and choices. Drawing together results from literature reviews and a qualitative online questionnaire, we discuss the everyday practices of social gamers in their interaction with games as algorithmic, programmed spaces. What is apparent from our discussion is that social games offer a multi-faceted microcosm for a closer analysis of the nuanced interplay of algorithms, data acquisition management and player visibility tactics understood in a broad sense.